Transiting Sub-stellar companions of Intermediate-mass stars - Sebastian, Daniel; Guenther, Eike W.; Heber, Ulrich; Geier, Stephan; Grziwa, Sascha (2015)
We use the CoRoT-survey to search for transiting close-in planets of intermediate-mass stars (M-* = 1.3 - 2.1 M-circle dot). We present recent results of our survey. RV-surveys and direct imaging campaigns showed, that intermediate-mass main-sequence stars have more massive planets then solar-like stars. Even brown dwarfs have been found. In our study we concentrated on short-period planets for which a mass-determination is possible. The detection of close-in planets of intermediate-mass stars put strong constraints on the timescales of the formation and migration. We already have identified transiting Jupiter-like planet candidates with short orbital periods and observed these candidates with high-resolution echelle-spectrographs at various Telescopes.